2010
DOI: 10.1111/j.1478-3231.2010.02367.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of periductal Langerhans cells and biliary epithelial cell-derived macrophage inflammatory protein-3α in the pathogenesis of primary biliary cirrhosis

Abstract: LCs existing around or within biliary epithelial layers are important as periductal antigen-presenting cells in PBC and the migration of LCs into bile ducts is closely associated with the periductal cytokine milieu and biliary innate immunity in PBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 28 publications
4
32
0
1
Order By: Relevance
“…This remarkably poor polymorphism, which was confirmed by sequencing exons 2 and 3 of the HLA-DQA2 and -DQB2 genes in a panel of HLA-DR, DQA1, DQB1 and DPA1 homozygous IHW cell lines, is reminiscent of the CD1 molecule system; it suggests that HLA-DQa2/b2 antigenic ligands share conserved biochemical or biophysical properties, which would make their characterization crucial. It is worth noting that LCs are also present in oral and genital mucosae, and cells expressing Langerin have been described in the human lung (30), liver (31) and cornea (32). Determining whether the HLA-DQA2 and -DQB2 genes are likewise expressed in such Langerin-positive DCs residing in tissues outside the skin might provide a clue as to the function of HLA-DQa2/b2 molecules and why their expression appears to be confined to LCs.…”
Section: Discussionmentioning
confidence: 99%
“…This remarkably poor polymorphism, which was confirmed by sequencing exons 2 and 3 of the HLA-DQA2 and -DQB2 genes in a panel of HLA-DR, DQA1, DQB1 and DPA1 homozygous IHW cell lines, is reminiscent of the CD1 molecule system; it suggests that HLA-DQa2/b2 antigenic ligands share conserved biochemical or biophysical properties, which would make their characterization crucial. It is worth noting that LCs are also present in oral and genital mucosae, and cells expressing Langerin have been described in the human lung (30), liver (31) and cornea (32). Determining whether the HLA-DQA2 and -DQB2 genes are likewise expressed in such Langerin-positive DCs residing in tissues outside the skin might provide a clue as to the function of HLA-DQa2/b2 molecules and why their expression appears to be confined to LCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these cytokine milieus, the damaged bile ducts and/or portal tracts show an increased susceptibility to PAMPs and enhanced production and secretion of innate inflammatory mediators in PBC [15,29]. PAMPs directly induce the production of MIP-3α in human BECs [23].…”
Section: Antigen-presenting Cells and Biliary Innate Immunity In Pbcmentioning
confidence: 99%
“…Several recent studies investigating biliary innate immunity support the thesis that cholangiocytes express a variety of Toll-like receptors (TLRs) or other pathogen-recognition receptors, and hypothesized that changes in the components of the innate immunity may be a prerequisite not only for the initiation but also for maintenance of the autoimmune attack [63,64,65,66]. Peroxisome proliferator-activated receptor-γ is constitutively expressed in cholangiocytes isolated from small intrahepatic bile ducts.…”
Section: Innate Immunity and Pbcmentioning
confidence: 99%
“…Harada et al [64] have shown by immunochemistry that langerin-positive Langerhans cells (LCs) are predominantly within or scattered around biliary epithelial layers of destructed bile ducts of PBC samples. Cytokines (IL-1β, TNF-α and IL-17) and PAMPs cultured human BECs induced macrophage inflammatory protein-3α, an LC-attracting chemokine.…”
Section: Innate Immunity and Pbcmentioning
confidence: 99%
See 1 more Smart Citation